(untitled) (One Health Journal of Nepal, 2023)
Introduction: Urinary tract infection (UTI) is a common reason for pediatric hospital visits, often leading to misdiagnosis due to nonspecific symptoms. This study aimed to establish the diagnosis of UTI using dipstick tests in children with or without localizing signs and symptoms of UTI. Also comparison between urine culture with a dipstick test for diagnosing UTI was done. Methods: A diagnostic study included 134 children aged 1 to 60 months presenting with fever or clinical signs of UTI. Urine samples were collected and subjected to culture, routine microscopy, and dipstick testing. The dipstick’s leukocyte esterase (LE) test and nitrite test were compared to urine culture to assess their diagnostic accuracy. Results: Among the 134 cases, 13 were culture positive, with E. coli being the most commonly isolated organism (53.8%). Fever was the most common symptom. Urine microscopy was positive in 21 cases, and 11 were culture positive. Compared to urine culture, the LE test had a sensitivity of 76.92%, specificity of 84.29%, PPV of 34.48%, and NPV of 97.14%. The nitrite test had a sensitivity of 84.61%, specificity of 92.56%, PPV of 55%, and NPV of 98.24%. Comparing either test to urine culture, the sensitivity was 92.30%, specificity was 82.64%, PPV was 36.36%, and NPV was 99.01%. Conclusions: The combined dipstick test, including the nitrite and LE tests, showed good sensitivity, specificity, and NPV compared to urine culture. It can be reliably used for diagnosing UTI and initiating antibiotic treatment while awaiting urine culture results.